2002
DOI: 10.1113/jphysiol.2002.022970
|View full text |Cite
|
Sign up to set email alerts
|

A stretch‐activated anion channel is up‐regulated by the malaria parasite plasmodium falciparum

Abstract: A recent study on malaria‐infected human red blood cells (RBCs) has shown induced ion channel activity in the host cell membrane, but the questions of whether they are host‐ or parasite‐derived and their molecular nature have not been resolved. Here we report a comparison of a malaria‐induced anion channel with an endogenous anion channel in Plasmodium falciparum‐infected human RBCs. Ion channel activity was measured using the whole‐cell, cell‐attached and excised inside‐out configurations of the patch‐clamp m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 18 publications
3
103
0
Order By: Relevance
“…anion conductance in uninfected non-CF red blood cells (17). Taken together, these data for the first time indicate a functional expression of CFTR in control but not in CFTR ⌬Phe-508/⌬Phe-508 red blood cells.…”
Section: Resultssupporting
confidence: 57%
“…anion conductance in uninfected non-CF red blood cells (17). Taken together, these data for the first time indicate a functional expression of CFTR in control but not in CFTR ⌬Phe-508/⌬Phe-508 red blood cells.…”
Section: Resultssupporting
confidence: 57%
“…The buffy coat containing platelets and white cells was removed by suction after each wash. After the last wash, the cells were suspended at 50% hematocrit in RPMI medium 1640. P. falciparum clone 3D7 was grown in human RBCs as described previously (7,22). 5.…”
Section: Methodsmentioning
confidence: 99%
“…Recent whole-cell electrophysiological studies of human erythrocyte membrane in serum-free isotonic conditions showed that infection by P. falciparum activates, at the trophozoite stage, a membrane conductance 100-to 150-fold larger than in uninfected cells (6)(7)(8)(9). The typical electrophysiological signature of infection is characterized by whole-cell current-voltage (I-V) curves showing inward rectification [lower current at positive membrane potential (Vm) than at negative values], anion selectivity, and inhibition by furosemide and 5-nitro-2-(3-phenylpropylamino)-benzoate (NPPB).…”
mentioning
confidence: 99%
“…Although several reports have suggested that PSAC activity results from the modification of host RBC proteins (13)(14)(15), none of these mutually exclusive proposals has been independently confirmed. In particular, we were unable to reproduce these reports despite intensive efforts (10).…”
mentioning
confidence: 98%